Enhancing consumer protection via price control in Malaysia - Ahmad Sharif, Nurretina; Yusoff, Rosnelim (2013)
Price control is an instrument of economic policy for correcting distortions in the relative price structure, resource allocation and income distribution caused by market imperfections. Price control legislations have been used by governments in restraining inflation and overcoming shortages of goods. Nevertheless, the issue remains whether the existing legal framework governing the price control mechanism is able to provide a comprehensive protection for consumers? This paper analyzes the legal and administrative mechanism which has been designed to manage price control in Malaysia. The mechanism used is explained by examining the provisions under Price Control and Anti Profiteering Act 2011 (Act 723). The paper also explores the legal issues associated with the existing price control legislation. This research is essentially a qualitative legal research whereby the materials used are obtained from libraries, archives and other databases. Applying a systematic inquiry or investigation of the factual data and theoretical concepts of rules and legal principles, the data is analyzed using analytical and critical analysis. The research finds that one of the aims of price control is to prevent traders and businesses from unscrupulously charging exorbitant prices for their goods and services and thus price control legislation can be seen to act as a safeguard for consumers against opportunistic profiteers. This paper concludes that in view of consumer protection, there are major improvements on managing price control under the new Act 723, however there are also limitations and weaknesses that can be considered and corrected for further improvement.